SOCIAL MEDIA AND RELIGIOUSITY: SHIFTING THE LIFESTYLE PARADIGM OF URBAN MUSLIM STUDENTS - Anwar, Khairil; Surawan, Surawan; Awang, Sarimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
The increasingly massive development of social media presents various spectacles that can be consumed by the general public. Along with the rise of social media, many things have changed, one of which is religion. This requires that da'wah in the digital era needs to make modifications and make peace with the growing media. The increasingly massive use of social media allows it to have a positive or negative impact on a person. The purpose of this study was to determine the contribution of accessing the use of social media to religious attitudes in students. The method used is quantitative with a correlational type. Data collection techniques through questionnaires and documentation. The data analysis technique uses the product moment formula, and the coefficient of determination uses SPSS 18. The results of this study indicate that there is a positive contribution between activities in using social media and students' religious attitudes with a high category or equal to 0.684. Therefore, the higher the activity using social media, the more religious attitudes will increase. The next thing that needs to be considered is a wise attitude in using social media and filtering content that is contrary to religious norms. Social media usage activities will provide important contributions and follow relevant theoretical insights to examine the impact of Internet use on religious affiliation, behavior, and beliefs.